Safety, Tolerability, and Pharmacokinetics of Single Ascending Doses of ELX‐02, a Potential Treatment for Genetic Disorders Caused by Nonsense Mutations, in Healthy Volunteers - Leubitz, Andi; Frydman‐Marom, Anat; Sharpe, Neal; Duzer, John; Campbell, Kathleen C.M.; Vanhoutte, Frédéric (Clinical pharmacology in drug development, 2019)
ELX‐02 is an investigational synthetic eukaryotic ribosome–selective glycoside optimized as a translational read‐through molecule that induces read through of nonsense mutations, resulting in normally localized full‐length functional proteins. ELX‐02 is being developed as a therapy for genetic diseases caused by nonsense mutations. Two phase 1a, randomized, double‐blind placebo‐controlled, single‐ascending‐dose studies were conducted in healthy human subjects to evaluate the safety and pharmacokinetics of ELX‐02. Single subcutaneously injected doses of ELX‐02 between 0.3 mg/kg and 7.5 mg/kg showed an acceptable safety profile without severe or serious drug‐related adverse events, including a lack of renal and ototoxicity events. Injection of ELX‐02 resulted in a rapid time to peak concentration and elimination phase, with complete elimination from the vascular compartment within 10 hours. ELX‐02 area under the concentration‐time curve to infinity showed dose‐exposure linearity (24‐fold increase for a 25‐fold dose increase), and the maximum concentration showed dose proportionality (17‐fold increase for a 25‐fold increase). The mean apparent volume of distribution was dose dependent, suggesting an increased distribution and tissue uptake of ELX‐02 at higher doses. The primary route of excretion was in the urine, with the majority of the compound excreted unchanged. These results support the evaluation of the safety, pharmacokinetics, and efficacy of repeat dosing in future studies.